Lung cancer screening with volume computed tomography is cost-effective in Greece - Xuanqi Pan; Katerina Togka; Hilde ten Berge; Lisa de Jong; Harry Groen; Maarten J. Postma; Eleftherios Zervas; Ioannis Gkiozos; Christoforos Foroulis; Kyriaki Tavernaraki; Sofia Lampaki; Georgia Kourlaba; et al. (PLoS ONE, 2025)
Objective This study aimed to assess the cost-effectiveness of lung cancer screening (LCS) employing volume-based low-dose computed tomography (LDCT) in contrast to the absence of screening, targeting an asymptomatic high-risk population in Greece, leveraging the outcomes derived from the NELSON study, the largest European randomized control trial dedicated to LCS. Methods A validated model incorporating a decision tree and an integrated state-transition Markov model was used to simulate the identification, diagnosis, and treatments for a population at high risk of developing lung cancer, from a healthcare payer perspective. Screen-detected lung cancers, costs, life years (LYs), quality-adjusted life years (QALYs), and the incremental cost-effectiveness ratio (ICER) were predicted. Sensitivity and scenario analyses were conducted to assess the robustness and reliability of the model’s outcomes under varying parameters and hypothetical situations. Results Annual LCS with volume-based LDCT detected 17,104 more lung cancer patients at early-stage among 207,885 screening population, leading to 8,761 premature lung cancer deaths averted. In addition, in contrast to no screening, LCS yielded 86,207 LYs gained and 50,207 incremental QALYs at an additional cost of €278,971,940, resulting in an ICER of €3,236 per LY and €5,505 per QALY, over a lifetime horizon. These estimates were robust in sensitivity analyses. Conclusions LCS with volume-based LDCT, targeting an asymptomatic high-risk population, is highly cost-effective in Greece. Implementing LCS ensures efficient allocation of public healthcare resources while delivering substantial clinical benefits to lung cancer patients.